Species Diversity and Potential Utilization of Moraceae in Nglanggeran Ancient Volcano, Gunungkidul Regency, Yogyakarta - Reinatawas Febri Santika; Ratna Susandarini (Journal of Tropical Biodiversity and Biotechnology, 2020)
Nglanggeran Ancient Volcano is one of the ecotourism areas in Gunungkidul Regency, Yogyakarta. This ancient volcano is one of the geological sites in Pegunungan Sewu. Pegunungan Sewu is a National Geopark in Indonesia and has been designated as a UNESCO Global Geopark since 2015. The determination of an area into a National Geopark and Global Geopark makes the biodiversity in the area must be protected and preserved, including the plant diversity, one of which is Moraceae. The ecological and economic importance of Moraceae in Nglanggeran Ancient Volcano has not been documented properly. This fact encourages the need to do this research. The aim of this research was to record species diversity of Moraceae and its potential uses. The research was conducted in August-November 2019 at Nglanggeran Ancient Volcano and followed by data analysis in Plant Systematic Laboratory, Faculty of Biology, Universitas Gadjah Mada. The samples were collected at two different tracks, covering the track to the peak and the pathway down. There were six species found, namely Artocarpus altilis (Parkinson) Fosberg, Artocarpus heterophyllus Lam., Ficus benjamina L., Ficus septica Burm. f., Maclura cochinchinensis (Lour.) Corner, and Streblus taxoides (Roth) Kurz. The potential uses of Moraceae by local people were identified from the interview and enriched by data from literature studies indicated that Moraceae plants were used as a food, medicine, for construction, soil protection plants, and houseplant.